The Place of Interest in the Theory of Production - Lange, Oskar (Review of Economic Studies, 1936)
Journal Article The Place of Interest in the Theory of Production Get access Oskar Lange Oskar Lange Ann Arbor, Michigan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 159–192, https://doi.org/10.2307/2967626 Published: 01 June 1936